Evaluation and implementation of distance learning: Technologies, tools and techiques - Belanger, France; Jordan, Dianne H.
his book is published by Idea Group Publishing. The book consists of seven chapters, a bibliography and references section, four appendices, an index, and author biography. In appendix A, there are three data forms those can used by distance learning course designers. In appendix B, under the title of ?definitions?, there is a dictionary consists of Internet and e-learning terms. In appendix C, there is a table relevant to infrastructure survey and upgrade requirements. Finally appendix D contains a list of web sites that offer discussions of distance learning issues and concepts. Two authors from USA have contributed to the book. France Belanger is an assistant professor of information systems in the Department of Accounting and Information Systems and a researcher for the Center for Global Electronic Commerce at Virginia Polytechnic Institute and State University. Prior to her academic career, Dr. Belanger held various technical, marketing, and managerial positions in large information systems and telecommunications firms and has provided consulting services to corporations in Florida. Her research interests focus on the impacts of distributed communication technologies on organizations. She has presented her work at several national conferences and has published in Information Management, The Information Society: An International Journal, and the Journal of Information Systems Education. Dianne H. Jordan is a strategic information technology planner at Booz Allen y Hamilton, where she focuses on advanced distributed learning initiatives. She recently completed a strategic evaluation of over 1,000 technical training and education courses for the U.S. Air Force. She has 20 years of professional experience in private industry, academia, and the federal government. She served as the CyberCongress Project Manager for the U.S. House of Representatives and was on the faculty at Baruch College (CUNY) where she taught telecommunications and the use of information technology for strategic advantage. She has been the senior federal manager in the Department of Defense. Dr. Jordan has a Ph.D. in Information Systems from the University of South Florida. These authors are from different backgrounds, institutions, and experiences. Both of them have strong professional backgrounds, which help them address the issues both from theoretical and practical perspectives. First chapter provides an overview of distance learning, including definitions of concepts and terms, an overview of learning variables in the distributed learning environment, and objectives of the book. Chapter two presents an in-depth review of the learning theories and variables that apply to distance learning. Of particular interest is a theory-based discussion of learning objectives in the cognitive, psychomotor, and affective domains, with attendant discussion as to how and to what degree instructional technologies might be appropriately employed to meet those objectives. 99 Chapter three introduces six distance learning technologies: computer-based training, videotape, computer-aided instruction, web-based training, teleconferencing, and video tele-training. In the book, each technology is described in detail, including design, equipment, access requirements, and the advantages and disadvantages of each technology for learners, instructors, and institutions. Chapters four through six are dedicated to analysis, design, and implementation of a distance learning project. In chapter four, the reader is presented guidelines for media conversion analysis. The chapter includes the steps that are determining distance learning suitability, portion of the course, selection of appropriate media, determining required time, pricing the cost, and doing cost/benefit analysis for a media conversion analysis. Chapter five present topics related to multimedia development for delivery in a distance learning environment. The chapter includes topics that are discussion of file and format specifications for digital multimedia, levels of courseware complexity, steps in the courseware development process, COTS (commercial off-the-shelf) tools for developing multimedia instruction content and CMI (computer managed instruction). Chapter six provides guidelines for implementing and evaluating distance learning courses and programs. This chapter outlines the issues, processes and practical tips for implementing and evaluating distance learning initiatives. Readers, particularly administrators, may take great interest in the organized step-by-step approach described. The authors describe the ?bandwagon? phenomena: ?small efforts by motivated individuals outside of the strategic planning process, with little or no support or funding.? They warn that the resulting small successes should not dictate the direction of an organization?s entire distance learning initiative. This chapter also includes a brief theory-based discussion of several useful evaluation models. Finally, Chapter seven presents three fictional case studies outlining the evaluation and implementation processes performed for the conversion of training courses to distance learning. The first case covers the strategic analysis, the second case introduces a course conversion analysis, and the third case presents an infrastructure analysis. Each case focuses on a different aspect of the analysis for distance learning. The relation of the book titles and subtitles is some confusing. There are many tables in the chapters but there is not tables list in the book. Besides, there is not a preface in the book. However, Chapter one can used instead of preface. In conclusion, the book focuses on the dominant processes, techniques, and tools that have been used to successfully plan, implement, and operate distance learning projects. It will be informative and useful for professionals and educators who are interested in preparing themselves for the transition from traditional learning to the emerging distance learning environment.